2007
DOI: 10.1152/ajpheart.01225.2006
|View full text |Cite
|
Sign up to set email alerts
|

Asynchrony of ventricular activation affects magnitude and timing of fiber stretch in late-activated regions of the canine heart

Abstract: Coppola BA, Covell JW, McCulloch AD, Omens JH. Asynchrony of ventricular activation affects magnitude and timing of fiber stretch in late-activated regions of the canine heart. Am J Physiol Heart Circ Physiol 293: H754-H761, 2007. First published April 20, 2007; doi:10.1152/ajpheart.01225.2006.-Abnormal electrical activation of the left ventricle results in mechanical dyssynchrony, which is in part characterized by early stretch of late-activated myofibers. To describe the pattern of deformation during "prest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…These findings support an important role for effective local preload as the cause of the regional differences in contraction pattern during asynchronous activation. However, Coppola et al (2007) also found evidence that the increased systolic shortening in late activated regions may be due to decreased afterload.…”
Section: Simulation Of Mechanical Dyssynchrony-possiblementioning
confidence: 96%
“…These findings support an important role for effective local preload as the cause of the regional differences in contraction pattern during asynchronous activation. However, Coppola et al (2007) also found evidence that the increased systolic shortening in late activated regions may be due to decreased afterload.…”
Section: Simulation Of Mechanical Dyssynchrony-possiblementioning
confidence: 96%
“…While the increased work can mostly be explained by the time-varying elastance of cardiac muscle, the decreased work in muscles stretched after the peak of the Ca 2ϩ transient is largely due to myofilament deactivation. dyssynchrony; hypertrophy; muscle mechanics; papillary muscle; stretch DYSSYNCHRONOUS ELECTRICAL ACTIVATION of the ventricles, due to conduction defects such as left bundle branch block or ventricular pacing of structurally normal hearts, leads to abnormal systolic stretch (2). During ectopic ventricular pacing, early contraction near the pacing site stretches remote sites that have not yet begun to contract (17).…”
mentioning
confidence: 99%
“…Because dyssynchronous systolic stretch is caused directly or indirectly by the contraction of earlier or later activated regions of the wall, its duration is relatively long and typically about half the normal systolic interval (2). Its magnitude and timing relative to local electrical activation depend on location relative to the stimulus site, with the largest and earliest systolic stretches occurring in the latest activated regions where premature lengthening has peaked and largely recovered by the time local depolarization occurs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such electromechanical dispersion of contractile activity may affect LV function, resulting in global LV dyssynchrony 15 and systolic and diastolic dysfunction. 16 Accordingly, the optimization of electromechanical activity by improving pre-ejection shortening-stretch mechanics may influence global LV performance and explain the benefits of CRT.…”
Section: Discussionmentioning
confidence: 99%